2003
DOI: 10.1038/sj.embor.embor873
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray structure of human acid‐β‐glucosidase, the defective enzyme in Gaucher disease

Abstract: Gaucher disease, the most common lysosomal storage disease, is caused by mutations in the gene that encodes acid-β-glucosidase (GlcCerase). Type 1 is characterized by hepatosplenomegaly, and types 2 and 3 by early or chronic onset of severe neurological symptoms. No clear correlation exists between the ~200 GlcCerase mutations and disease severity, although homozygosity for the common mutations N370S and L444P is associated with nonneuronopathic and neuronopathic disease, respectively. We report the X-ray stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
288
0
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(312 citation statements)
references
References 37 publications
13
288
0
11
Order By: Relevance
“…Notably, in our study, this allele was detected only in type 1 patients and was revealed to be the most common allele (10/28 alleles, approximately 36% prevalence) in type 1 patients, suggesting that this mutation may predispose to type 1 GD, which precludes neurological involvement. A previous report suggested that based on the X-ray structure of GBA, amino acid change involving the glycine residue (G46) located in the noncatalytic domain II might have relatively minor influence on GBA structure and, therefore, catalytic activity [18]. One homozygous G46E/G46E mutation found in our study was in a female patient (case No.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…Notably, in our study, this allele was detected only in type 1 patients and was revealed to be the most common allele (10/28 alleles, approximately 36% prevalence) in type 1 patients, suggesting that this mutation may predispose to type 1 GD, which precludes neurological involvement. A previous report suggested that based on the X-ray structure of GBA, amino acid change involving the glycine residue (G46) located in the noncatalytic domain II might have relatively minor influence on GBA structure and, therefore, catalytic activity [18]. One homozygous G46E/G46E mutation found in our study was in a female patient (case No.…”
Section: Resultsmentioning
confidence: 52%
“…Because phenylalanine (F213) and arginine (R257) residues are known to be located in α-helices 3 and 4 of the catalytic domain III of GBA [18], F213I and R257Q mutations may be associated with severe type 2 and/or 3 GD. In fact, the F213I allele was reported to be associated with a severedisease phenotype [20,21]; however, it was found in all 3 types of Korean GD patients, including 3 type 1, 1 type 2, and 4 type 3 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual inspection of GBA three-dimensional structure 14 (PDB code 1OGS) and amino-acid substitutions were carried over using the program Coot; 15 energy minimization using the program DISCOVER3 from the InsightII program suite (Accelrys, Inc., San Diego, CA, USA). Figures were drawn using the program Chimera.…”
Section: Structural 3d Analysismentioning
confidence: 99%
“…All mutated residues belong to domain III, which contains the catalytic site 14 (Figure 2). Significantly, the computational analysis revealed that, apart from p.P198S (P159S), p.G304R (G265R) and p.E365K (E326K), all mutations are directly or indirectly involved in substrate recognition (Supplementary Table S2).…”
Section: Structural Analysismentioning
confidence: 99%